Liquidity, Profitability and Operational Costs on Corporate Income Tax - Bertilia Lina Kusrina; Putri Desti Fatwah Fatimah (Yayasan Ilomata, 2021)
Tax revenue is the largest source of income for the Indonesian state. One of the contributors to state revenue from the tax sector is corporate income tax. Financial performance is one measure of the success of a business entity which is expected to increase revenue from corporate income tax. This study aims to determine the effect of financial performance using variable liquidity ratios, profitability ratios, and operating costs on corporate income tax. The data used is secondary data, namely annual financial report data from large trading sub-sector companies (wholesale) listed on the Indonesia Stock Exchange (IDX) for the 2014-2018 period. The analytical method used is multiple regression analysis. The results showed that partially profitability and operating costs have an effect on corporate income tax, while liquidity has no effect on corporate income tax. Simultaneously, liquidity, profitability and operating costs affect corporate income tax. Based on the results obtained that the ratio that affects corporate income tax is profitability and operating costs, so as an implication the internal party/management must be careful with the information presented in the financial statements which will have a negative impact on the users of financial statements, especially on operating costs.